Identifikasi dan Karakterisasi Sumber Daya Genetik Buah-buahan Lokal di Kabupaten Bangli - MARTINI, NI LUH; DWIYANI, RINDANG; PRADNYAWATHI, NI LUH MADE (Agrotrop : Journal on Agriculture Science; Vol 5 No 2 (2015), 2015)
Identification And Characterization Of Local Fruits Genetic Resources In BangliRegency. Local fruit is all kinds of fruits that are cultivated in Bali. This study aims toidentify the types of local fruits grown in Bangli Regency; to create profile about those localfruits based on morphological and agronomic character, usability, production, andphotographs of genetic resources; to create a map regarding geographical destination of thefruit. This study was conducted in Bangli Regency consisting four districts i.e District ofBangli, Susut, Kintamani, and Tembuku. The experiment was conducted for six months, fromJanuary to June 2015. The research consisted of three stages of activities: (1) collection ofsecondary data, (2) surveys the types of genetic resources and distribution, (3) identificationof morphological and agronomic characters of genetic resources, growing environment andbenefit of local fruits. The results showed that the observations in the field found 36 speciesand 68 sub-species of local fruits spread over four districts. Based on the value of LocationQuotient (LQ) Bangli District has two main commodities including citrus, in which Awanvillage is the central production region, and banana, in which Subaya village in the centralproduction region.
Keywords: Identification, Characterization, Genetic resources, Local Fruits